2019
DOI: 10.1098/rsif.2019.0125
|View full text |Cite
|
Sign up to set email alerts
|

Repeated evolution of drag reduction at the air–water interface in diving kingfishers

Abstract: Piscivorous birds have a unique suite of adaptations to forage under the water. One method aerial birds use to catch fish is the plunge dive, wherein birds dive from a height to overcome drag and buoyancy in the water. The kingfishers are a well-known clade that contains both terrestrially foraging and plunge-diving species, allowing us to test for morphological and performance differences between foraging guilds in an evolutionary context. Diving species have narrower bills in the dorsoventral and sagittal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…Similar results are reported by Crandell et al. (2019) after correcting for body size. However, they showed that beak width was the only trait with significant difference between foraging regimes after phylogeny was taken into account.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results are reported by Crandell et al. (2019) after correcting for body size. However, they showed that beak width was the only trait with significant difference between foraging regimes after phylogeny was taken into account.…”
Section: Discussionsupporting
confidence: 91%
“…Predicted impact forces were significantly correlated with recent empirical values (Crandell et al. 2019) of deceleration from 3D printed beaks (PGLS; P = 0.0061, N = 25; see Fig. S13).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Birds such as northern gannets and kingfishers dive into water to catch prey (Chang et al. 2016; Crandell, Howe & Falkingham 2019). These interesting biological behaviours have inspired the development of water-running robots and shape-morphing aerial unmanned vehicles (Floyd et al.…”
Section: Introductionmentioning
confidence: 99%
“…In functional ecology, key questions often involve studying the impact of specific morphological properties of the organism (or part of it). For example, heads of bat species were scanned and 3D printed for their aerodynamical properties to be tested in a wind tunnel (Vanderelst, Peremans, Razak, Verstraelen, & Dimitriadis, 2015); similarly, 3D printed beaks of kingfishers were used to study the evolution of drag reduction at the air-water interface (Crandell, Howe, & Falkingham, 2019). 3D printing furthermore allows to go one step further than replicating biological material: creating highly controlled variants in order to manipulate morphological features independently.…”
Section: Introductionmentioning
confidence: 99%